Postal pleasures sex, scandal, and Victorian letters - Thomas, Katie-Louise. (New York ; Oxford : Oxford University Press, 2012)
With readings of novels by Thomas Hardy, Anthony Trollope, Oscar Wilde, Bram Stoker, Henry James, and others, this work explores the relationship between illicit sex and the postal service in Victorian Britain.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Letter writing -- Great Britain -- History -- 19th century; Literature and society -- Great Britain -- History -- 19th century; Postal service -- Great Britain -- History -- 19th century; Scandals -- Great Britain -- History -- 19th century; Letter writing recreations; Homosexuality -- Great Britain -- History -- 19th century